Comparative physiological, morphological, histological, and AQP2 immunohistochemical analysis of the Arabian camels (Camelus dromedarius) and oxen kidney: Effects of adaptation to arid environments - El-Hady, Enas; Behairy, Amany; Goda, Nehal A.; Abdelbaset-Ismail, Ahmed; Ahmed, Ahmed E.; Al-Doaiss, Amin A.; Abd El-Rahim, Ibrahim; Alshehri, Mohammed A.; Aref, Mohamed (Frontiers in Animal Science, 2023)
The purpose of this study was to explore how evolutionary adaptation to arid conditions modifies the kidney characteristics in Arabian camels (Camelus dromedarius) compared to oxen. Urine samples were physically and chemically analyzed. Harvested kidneys were subjected to topographical and fast spin echo (FSE) MR imaging. Histology, histomorphometry, and AQP2 expression by immunohistochemistry were also performed. Here, in dromedaries, sodium and potassium values in the urine were much higher (p=0.001, for both), whereas chloride was much lower (p=0.004) than the values of oxen. Compared with oxen, the level of the hormone aldosterone in serum was significantly lower (p=0.002), whereas creatinine and urea were significantly higher (p=0.005 and p=0.001, respectively). Uric acid in dromedaries and oxen did not differ significantly (p=0.349). Like sodium levels (p=0.001) in dromedary serum, chloride was also much higher (p=0.002) than in oxen. The average value of potassium was much lower (p=0.009) than that of oxen. Morphologically, anatomical and FSE MRI studies revealed that minor and major calyces were not found in dromedary kidneys. In oxen, the renal pelvis was not found, and the major calyx was directly connected to the ureter. The dromedary kidney contained a wider medullary portion as well as increased diameters for renal corpuscles (RCs), proximal convoluted tubules (PCTs), and collecting tubules (CTs, p<0.05) compared with the oxen. We also noted that AQP2 was significantly expressed in dromedary nephron components, except for RCs, compared with oxen as shown by immunohistochemistry. Overall, these data strongly suggest that the dromedary has a greater ability to adapt to harsh desert conditions in terms of producing highly concentrated urine than oxen.